Ischemic necrosis of the hand due to radial artery catheterization - Nin Ferrari, José; Artucio, Héctor (Cirugía del Uruguay, 1979)
The author describes a case of ischemic necrosis of hand following punction of radial artery by Teflon catheter. The paper includes a review of indications and complications of percutaneous punction of radial artery. Existing literature refers to 8 cases in which this complication appeared; they are rare but grave and consequently certain precautions, indicated in this article, should be taken to prevent it.